G. R. Elton, Policy and Police. The Enforcement of the Reformation in the Age of Thomas Cromwell - Izdebski, Hubert (Czasopismo Prawno-Historyczne, 1973)
Recenzja: G[eoffrey] R[udolph] Elton, Policy and Police. The Enforcement of the Reformation in the Age of Thomas Cromwell, Cambridge 1971, University Press.